Rehabilitation of COVID 19 patients, a review of literature (Bangladesh Journal of Neuroscience, 2026)
The global outbreak of coronavirus disease 2019 has created an unprecedented challenge to the society. Currently, the United States stands as the most affected country, and the entire healthcare system is affected, from emergency department, intensive care unit, post-acute care, outpatient, to home care. Considering the debility, neurological, pulmonary, neuromuscular, and cognitive complications, rehabilitation professionals can play an important role in the recovery process for individuals with coronavirus disease 2019. Many patients presenting with COVID-19 will have no specific airway clearance needs. There have been no reports of COVID-19 positive patients having high secretion loads that would require intensive chest physiotherapy or postural drainage. In Bangladesh in ICU settings physiatrist or physiotherapists are not directly involve in respiratory care management but in mild to moderate case or post-acute care breathing exercises, other musculoskeletal exercises, bed positioning and pressure sore care are advised. This review reveals the global concerns of rehabilitation need of COVID 19 patients.